Nilai-Nilai Dakwah dalam Strategi Komunikasi Pemasaran Kerajinan Aluminium: Studi pada Toko Sakinah Group Aluminium Sumatera Selatan - Dwi Lestari, Ayu; Randicha Hamandia, Muhammad; Syarifudin, Achmad (Journal of Islamic Communication Studies, 2023)
Aluminum crafts processed into various kitchen utensils are characteristic of Tanjung Atap Village, Tanjung Batu District, Ogan Ilir Regency, South Sumatra. The village’s fame for aluminium crafts has made many people work as aluminium craftsmen, which is used as an economic field for them. In addition to the existence of aluminium craftsmen, some people set up shops to sell kitchen tools, such as the Sakinah Group Aluminium shop. However, in this village, several shops have been established to sell kitchen equipment. This then gave rise to competition for the Sakinah Group Aluminium Shop. The purpose of the study was to determine the marketing communication strategy for aluminium crafts at the Sakinah Group Aluminium Store, the da’wah values applied in marketing communications, and the obstacles to marketing communication strategies for aluminium crafts at the Sakinah Group Aluminium Store. This study uses a qualitative research method that uses descriptive data in the form of written or oral words from what has been studied with data collection techniques, namely observation, interview, and documentation. The results showed that the marketing communication strategy of the Sakinah Group Aluminium figures in Tanjung Atap village used the 4P marketing mix theory (product, price, place, and promotion) in Sakinah Group Store promotional activities using word-of-mouth communication, namely old customers recommending these kitchen tools for cooking to new customers. In addition, Sakinah Group Aluminium uses a shop identification board or banner that functions to provide information to consumers. The da’wah values applied in marketing communications at Sakinah Group Stores include the values of honesty, competition, and serving consumers well. In addition, the obstacle to Sakinah Group Aluminium Store's marketing communication strategy is that it has not yet implemented social media, so the products sold are not widely known by consumers.